2007
DOI: 10.1152/ajpcell.00602.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of endosomal Na+-K+-ATPase and cardiac steroids in the regulation of endocytosis

Abstract: Plasma membrane Na(+)-K(+)-ATPase, which drives potassium into and sodium out of the cell, has important roles in numerous physiological processes. Cardiac steroids (CS), such as ouabain and bufalin, specifically interact with the pump and affect ionic homeostasis, signal transduction, and endocytosed membrane traffic. CS-like compounds are present in mammalian tissues, synthesized in the adrenal gland, and considered to be new family of steroid hormones. In this study, the mechanism of Na(+)-K(+)-ATPase invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…A number of previous studies have also reported that external application of ouabain as well as other CGs results in internalization of both ␣ and ␤ subunits of the Na ϩ /K ϩ -ATPase. One role suggested for this process is acidification of endosomal pH (11,30). Other studies related this process to the activation of caveolar Src and the subsequent ouabain-induced signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have also reported that external application of ouabain as well as other CGs results in internalization of both ␣ and ␤ subunits of the Na ϩ /K ϩ -ATPase. One role suggested for this process is acidification of endosomal pH (11,30). Other studies related this process to the activation of caveolar Src and the subsequent ouabain-induced signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was suggested to be triggered by ouabain-induced activation of Src and to be involved in the signal transduction involved in translocation of the pump to the nucleus (9,10). Alternatively, it was proposed that ouabain-induced internalization may be a means of regulating endosomal pH (11) or a natriuresis mechanism induced by endogenous CG (12).…”
mentioning
confidence: 99%
“…The enhancing effect of bufalin on CYP24A1 expression may be mediated by both nuclear VDR expression and Erk MAP kinase activation. Bufalin has been shown to direct cytoplasmic membrane components adjacent to the nucleus by regulating endosomal pH and endocytosed membrane traffic in neuronal precursor cells most likely via a Na + ,K + -ATPase-mediated mechanism [37]. Since the relation between endosomal function and degeneration of exported nuclear proteins remains unknown, further investigation is required to elucidate the role of the Na + ,K + -ATPase in the regulation of nuclear proteins, including VDR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the binding of ouabain to Na ϩ -K ϩ -ATPase elicits numerous additional changes in cell function. These include activation of intracellular signal transduction (46), activation of cytoplasmaic Ca 2ϩ oscillation (2), stimulation of endocytosis, and inhibition of endocytosed membrane traffic (13,37), as well as cell proliferation (1) and adhesion (24). Because all of these molecular mechanisms were induced by ouabain in the nanomolar range, any of them could be involved in the physiological processes described in this study.…”
Section: Aorta Vascular Homeostasis and Bpmentioning
confidence: 98%